Competitive Advantage as a Mediation of the Influence of Green Banking and Corporate Governance on Company Value - Puspitasari, Rulita Indra; Saifi, Muhammad; Firdausi Nuzula, Nila (Profit: Jurnal Adminsitrasi Bisnis, 2024)
This research aims to explore the influence of Green Banking and Corporate Governance on Company Value through the mediation of Competitive Advantage in Conventional Commercial Banks listed on the Indonesia Stock Exchange (IDX) from 2017-2022. The study employs a quantitative method with a positivistic approach, involving a sample of 41 Conventional Commercial Banks listed on the IDX. This research uses a purposive sampling technique with inclusion criteria involving banks registered on the IDX, publishing financial reports, and providing the necessary data. Secondary data is in the form of banking financial reports for 2017-2022. Hypothesis testing uses quantitative statistical analysis with Structural Equation Modeling (SEM). The research results show that Green Banking and Corporate Governance significantly affect Competitive Advantage and Company Value. Competitive advantage and company value have a significant favourable influence. The findings of this research can contribute to a deeper understanding of the relationship between Green Banking, Corporate Governance, Competitive Advantage and Company Value in the context of the conventional banking industry in Indonesia.